1998
DOI: 10.1152/ajpregu.1998.275.5.r1563
|View full text |Cite
|
Sign up to set email alerts
|

Adenylyl cyclase activity and glucose release from the liver of the European eel,Anguilla anguilla

Abstract: The properties of adenylyl cyclase (AC) in liver membranes of the European eel ( Anguilla anguilla) and the involvement of cAMP in glucose release from isolated hepatocytes in response to catecholamines were studied. Basal enzyme activity seemed essentially unaffected by GTP, while a biphasic response to increasing nucleotide concentrations was obtained in the presence of epinephrine. Eel liver AC was dose-dependently stimulated by guanosine 5′- O-(3-thiotriphosphate) and inhibited by guanosine 5′- O-(2-thiodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Due to decrease of basal cytoplasmic and ER calcium levels and the increase of basal mitochondrial calcium level, we hypothesize that the mitochondria can pumping calcium from the cytoplasm and ER, as previously observed in some liver dysfunctions (Amaya and Nathanson, 2013). Some authors have also suggested the important role of calcium homeostasis in hepatic regulation in eels (Fabbri et al, 1998). This excess of calcium could then activate the mitochondrial biogenesis, confirmed by the increase in mitochondrial enzyme transcription atp6-8 and mitochondrial mass in our study.…”
Section: Discussionsupporting
confidence: 88%
“…Due to decrease of basal cytoplasmic and ER calcium levels and the increase of basal mitochondrial calcium level, we hypothesize that the mitochondria can pumping calcium from the cytoplasm and ER, as previously observed in some liver dysfunctions (Amaya and Nathanson, 2013). Some authors have also suggested the important role of calcium homeostasis in hepatic regulation in eels (Fabbri et al, 1998). This excess of calcium could then activate the mitochondrial biogenesis, confirmed by the increase in mitochondrial enzyme transcription atp6-8 and mitochondrial mass in our study.…”
Section: Discussionsupporting
confidence: 88%
“…In fish, increased energetic efficiency might be partially explained by a series of physiological responses that enhance the delivery of blood flow and thus O 2 supply to muscle, including elevated heart and gill rates during continuous swimming (Barron, Tarr, & Hayton, ; Korsmeyer, Lai, Shadwick, & Graham, ; Rodnick & Planas, ; Stevens & Randall, ). Furthermore, catecholamine upregulation may enhance arterial O 2 capacity via increased blood hematocrit (Randall & Daxboeck, ), while promoting glycogenolysis (glycogen‐to‐glucose conversion) and gluconeogenesis (lactate removal) in the liver of many fish species (Fabbri et al, ; Rodnick & Planas, ). Similar exercise‐related responses (e.g., elevated cortisol) also influence the duration of postexercise recovery and restoration of energy reserves in fish (reviewed in Rodnick & Planas, ).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, successive systemic adjustments are employed to match higher energy demands as swimming speed increases (reviewed in Rodnick & Planas, ). For instance, catecholamine upregulation enhances arterial O 2 capacity via increased blood hematocrit (Randall & Daxboeck, ), while promoting glycogenolysis (i.e., glycogen‐to‐glucose conversion) and gluconeogenesis (i.e., lactate removal) in the liver of many fish species (Fabbri, Barbin, Capuzzo, & Biondi, ). Although the mechanistic basis is not fully understood, studies have found that continuous swimming may accelerate the recovery of metabolite and acid‐base status and even prevent the plasma cortisol surge normally associated with exhaustive exercise (Milligan et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the growth rate between treated and untreated chondrocyte cultures can be explained as a possible interference that electromagnetic fields may have on the state of cells' electric charge, in terms of the ability of chondrocytes to restore the correct intracellular energetic equilibrium [30]. Moreover, the molecular mechanisms through which low-frequency electromagnetic fields could interfere with chondrocyte proliferation and differentiation have been partially clarified [31]. To evaluate the best efficacy of EMFs on cell culture conditions must mimic closely the in vivo environment of the cell type [32].…”
Section: Discussionmentioning
confidence: 99%